Comparison of Combination-Vaginal Clindamycin with Oral Metronidazole and Oral Metronidazole Alone in the Treatment of Bacterial Vaginosis - Rabia Sharif, Shazia Shaeen, Beenish Yousaf, Memoona Maqbool, Uzma Manzoor, Saba Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Bacterial vaginosis is the most common vaginal infection of sexually active woman. Bacterail vaginosis has been associated with preterm labour, amniotic fluid infection, chorioamniotiss and postpartum endometritis. Objective: To compare the efficacy of combination oral metronidazole-vaginal clindamycin gel with oral metronidazole alone in the treatment of bacterial vaginosis. Material and methods: This Randomized Controlled Trial was conducted in Gynaecology and Obstetrics Department, District Headquarter Hospital, Faisalabad. Approval from hospital Ethical Review Committee was taken after formulation of synopsis. 422 Patients fulfilling the inclusion criteria enrolled in the study. Informed consent was taken from each participant of the study. Patients was randomized into Group A and Group B using computer generated random number table. Results: Data was collected from 422 patients with mean gestational age 38.67 ± 1.69 weeks. The cumulative cure rate in the oral metronidazole group was 87% and 89.6% in the oral clindamycin group. There was no statistical difference in the efficacy of the two medications (p = 0.639). Nine (13%) of the women who received oral metronidazole and seven (10.4%) of the women in the oral clindamycin group had treatment failures following the test of cure, with an overall failure rate of 11.8%. Conclusion: It is concluded that both medications have comparable efficacy and similar pregnancy outcomes in the treatment of bacterial vaginosis. Keywords: Vaginosis, Prevalence, Woman, Postpartum